Creating a brand identity : a guide for designers - Slade-Brooking, Catharine (L. King, 2016)
Creating a Brand Identity goes behind the scenes to explore the creative processes involved in designing a successful brand identity, one of the most fascinating and complex challenges in graphic design.This bestselling book is ideal for students, professionals and agencies working in the fields of: •Graphic Design •Branding •Brand Management•Advertising •Marketing •Communications Authored by design and branding expert, Catharine Slade-Brooking,Creating a Brand Identityincludes exercises and examples that highlight the key activities undertaken by graphic designers to create successful brand identities, including:•Defining the audience•Analysing competitors•Creating mood boards•Naming brands•Logo design•Client presentations•Rebranding•Launching a new brand identityCase studies throughout the book are illustrated with brand identities from a diverse range of industries including digital media, fashion, advertising, product design, packaging, retail and more.The book uses images of professional design concepts, brand case studies and diagrams throughout to illustrate the text. Flow-charts are also used extensively to highlight the step-by-step methodology applied by industry professionals to create a brand.The content of the book has been derived from Catharine Slade-Brooking own experience of entering the world of branding as a graduate and having to learn the hard way, 'on the job'. This, in turn, enabled the author to develop teaching materials for undergraduate and postgraduate students on the BA Graphic Communication course at the University of the Creative Arts, where Slade-Brooking is a lecturer. The book has been recommended across a wide range of university courses, from graphic design school to animation, digital media, textiles and interior design. It includes a full glossary of brand terminology and a list of recommended further reading.